X. wyścig kolarski dookoła Polski. (Gdańsk : [s.n.], 1953)
Afisz inf. o wyśigu we wrześniu 1953 r.
Keywords: Kolarstwo -- Polska -- 1945-1970 -- druki ulotne; Sport -- Polska -- Gdynia -- 1945-1970 -- druki ulotne